Strategi Pengembangan dalam Meningkatkan Kualitas Produk Food And Beverage di Restoran Pegatoria Pegasus Stable Bogor - Daniel Jehovah; Benaya Dustin; Alvin Alexis; Budi Setiawan; Johann W.H. Prawiro (Yayasan Literasi Sains Indonesia, 2024)
This research investigates development strategies aimed at enhancing the quality of food and beverage offerings at Pegatoria, a restaurant situated in Pegasus Stable, Bogor Regency. Employing a descriptive qualitative approach, data were gathered through interviews and on-site observations with Pegatoria's management. The study reveals that the COVID-19 pandemic has significantly impacted visitor numbers and public awareness of the restaurant in this tourist destination. Several issues were identified, including a decline in product quality due to reduced patronage and visibility, alongside challenges in maintaining product standards as expected. In response to these challenges, development strategies focused on improving product performance, aligning product features with market demands, and selecting appropriate ingredients and packaging. The implementation of these strategies is anticipated to restore consumer confidence, bolster customer loyalty, and sustainably drive Pegatoria's business growth. Efforts to enhance product quality are pivotal in enhancing competitiveness and establishing the restaurant's reputation in the regional tourism industry. Consequently, this study contributes to the discourse on restaurant business development strategies amidst the evolving landscape of the tourism sector and the global pandemic's repercussions.